Recurrent Tuberculosis of Greater Trochanter and Its Bursa - Keshav S. Shenoy; Santosh S. Jeevannavar; Prasanna Baindoor; Sunil Mannual; Savith V. Shetty (Case Reports in Orthopedics)
A 65-year-old female had a history of tuberculosis of the left greater trochanter 30 years ago. She underwent 6 months of chemotherapy after which the disease healed completely. Currently she presented to us with pain and swelling on the lateral aspect of left hip of 2-month duration. Clinical and radiological findings were suggestive of a recurrence. Biopsy was conclusive for tuberculosis. She was successfully treated with debridement and curettage with chemotherapy for 1 year. Recurrent tuberculosis of the greater trochanter is rare and should be aggressively treated.